The influence of budget preparation, budget implementation and regulation on budget absorption with organizational commitment as a moderation variable in the government of southeast sulawesi province - SAUM FASIHU; KARTINI; DARMAWATI (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine and analyze the effect of participation in budget preparation, budget execution, and regulation on budget absorption, and how the influence of participation in budget preparation, budget implementation, and regulation on budget absorption is moderated by organizational commitment to the Provincial Government of Southeast Sulawesi. This type of research is quantitative research. The sample in this study was taken by 3 people in each regional apparatus organization (OPD), consisting of the head of service or secretary, the head of the sub-section of finance, and the head of the sub-division of planning so that a total of 75 respondents were obtained. The research instrument used was a questionnaire, where the data collected from the questionnaire would be analyzed using multiple linear regression analysis and moderation regression analysis. The results of this study indicate that participation in budget preparation, budget implementation, and regulation has an effect on budget absorption. This means that participation in budget preparation, budget implementation, and regulations can increase budget absorption. The results of the data analysis show that organizational commitment is able to strengthen the influence of participation in budget preparation, budget execution, and regulation on budget absorption.